High prevalence and risk factors of dropout intention among Chinese medical postgraduates. Issue 1 (31st December 2022) - Peng, Pu; Yang, Winson Fuzun; Liu, Yueheng; Chen, Shubao; Wang, Yunfei; Yang, Qian; Wang, Xin; Li, Manyun; Wang, Yingying; Hao, Yuzhu; He, Li; Wang, Qianjin; et al.
ABSTRACT: Background: A high attrition rate in medical students has exacerbated the physician shortage in China. However, few studies have explored the risk factors of dropout intention in medical postgraduates. This study compared the prevalence of dropout intention and mental distress between medical and non-medical postgraduates in China and investigated risk factors for dropout intention. This study also explored the impact of medical postgraduates' perception of the Chinese healthcare environment on their mental status and dropout intention. Methods: This cross-sectional study was conducted using online questionnaires from October 2020 to April 2021. Convenience sampling was used to recruit postgraduates in different majors. Outcomes included dropout intention and potential risk factors, including mental distress, quality of life, and fatigue. Medical postgraduates were additionally assessed for healthcare environment satisfaction, burnout, career choice regret, and experiences of workplace violence. A logistic regression model was constructed to evaluate the association between dissatisfaction, mental distress, and turnover intention. Results: A total of 740 medical and 670 non-medical postgraduates participated in the survey. The rates of depression symptoms (33.8% vs. 39.0%, p < 0.001), anxiety symptoms (22.2% vs. 32.4%, p < 0.001), and somatic symptoms (34.7% vs. 42.4%, p = 0.004) were lower in medical postgraduates, while more medical postgraduates (58.4% vs. 48.4%, p < 0.001) reported dropout intention. Dissatisfaction with the healthcare environment (odds ratio [OR]: 1.65; 95% confidence interval [CI]: 1.17–2.34, p = 0.005), career choice regret (OR: 6.23; 95% CI: 4.42–8.78, p < 0.001), and high perceived stress (OR: 2.74; 95%CI: 1.90–3.94, p < 0.001) remained independently associated with turnover intention. Conclusions: Mental distress is common among postgraduates, calling for timely interventions. Medical postgraduates reported higher turnover intention. Healthcare environment perception also affected the mental health and dropout intentions of medical students. A decent future income, reduced workload, shorter duration medical training, and better doctor-patient relationships are urgently needed.